Validation of online mindfulness-enhanced course for stress reduction in teachers - Ye, Qun; Huang, Ying; Ge, Xingcheng; Song, Xiaolan (Frontiers in Psychiatry, 2023)
Background: Mindfulness-based interventions have gained popularity as a means of reducing stress and increasing resilience among the preclinical population. The present study aimed to investigate the effects of an online mindfulness-enhanced course on stress reduction in teachers, especially since online learning and teaching have been frequently applied to respond to emergencies such as COVID-19-relevant school suspension. Methods: The study consisted of two phases. Phase 1 aimed to explore the relationship between teachers' perceived stress and mindfulness traits. 6252 teachers completed assessments of stress symptoms using the Chinese Perceived Stress Scale (CPSS) and occupational stress sources, as well as mindfulness using the Five Factor Mindfulness Questionnaire (FFMQ). Phase 2 aimed to examine the effectiveness of the online mindfulness-enhanced course. 132 teachers were randomly assigned to either receive a 3-week online mindfulness course specifically designed for stress reduction and emotion regulation (N = 66) or a matched active control group (N = 66) and their pre-training and post-training self-reported states (e.g., perceived stress, mindfulness level, practice time) were measured. Results: The detection rate of Health Risk Stress (≥ 26 scores) was as high as 61.72%, and a negative association between the score of FFMQ and perceived stress level was found. Importantly, compared to the control group, the mindfulness training group showed a significant decrease in perceived stress and negative emotion, as well as an increase in understanding of the core mechanisms of mindfulness after training. Additionally, individual improvement in FFMQ scores was predicted by practice time. Conclusions: The study showed a high percentage of teachers experiencing stress, and the data supported the reliability and validity of the brief online mindfulness-enhanced course designed to reduce stress and regulate emotion for frontline teachers.